1999
DOI: 10.1046/j.1365-8711.1999.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

The formation mechanism of molecular hydrogen on icy mantles of interstellar dust

Abstract: The fundamental processes of H2 formation via H + H → H2 on the surfaces of icy mantles of interstellar dust have been investigated consistently within a single model based on a classical molecular dynamics (MD) computational simulation. As a model surface for icy mantles of dust grains, an amorphous water ice slab was generated at 10 and 70 K under periodic boundary conditions. The first and second incident H atoms were then ‘thrown’ on to the model surface. Two MD procedures were employed: (i) the H2)O molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…our MD simulation (Takahashi et al, 1999a). It was found that the ejection process of the product H 2 via the direct ejection mechanism occurred subsequently after the two H atoms' reaction process.…”
Section: Ejection Process Of a Molecular Hydrogenmentioning
confidence: 82%
See 3 more Smart Citations
“…our MD simulation (Takahashi et al, 1999a). It was found that the ejection process of the product H 2 via the direct ejection mechanism occurred subsequently after the two H atoms' reaction process.…”
Section: Ejection Process Of a Molecular Hydrogenmentioning
confidence: 82%
“…The present definition of the reaction probability is not a global one, but a microscopic one. The results are shown in Table 5 (after Takahashi et al, 1999a) and they are found to be almost unity.…”
Section: Reaction Process Of Two Hydrogen Atomsmentioning
confidence: 90%
See 2 more Smart Citations
“…In the Langmuir-Hinshelwood mechanism, the adsorbed H atoms quickly equilibrate and diffuse on the surface of the grain either by thermal activation or by tunneling. When two adsorbed H atoms encounter each other, an H 2 molecule may form (Williams 1968;Hollenbach & Salpeter 1970;Smoluchowski 1981;Aronowitz & Chang 1985;Duley & Williams 1986;Pirronello & Averna 1988;Sandford & Allamandolla 1993;Takahashi et al 1999;Farebrother et al 2000). The steady-state production rate of molecular hydrogen, R H2 (cm −3 s −1 ) can be expressed by…”
Section: Introductionmentioning
confidence: 99%